2020
DOI: 10.1186/s12889-020-08967-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient and health system delay among TB patients in Ethiopia: Nationwide mixed method cross-sectional study

Abstract: Background: Effective tuberculosis (TB) control is the end result of improved health seeking by the community and timely provision of quality TB services by the health system. Rapid expansion of health services to the peripheries has improved access to the community. However, high cost of seeking care, stigma related TB, low index of suspicion by health care workers and lack of patient centered care in health facilities contribute to delays in access to timely care that result in delay in seeking care and henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
40
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 40 publications
12
40
3
1
Order By: Relevance
“…These two papers imply that subjective misevaluation of disease severity, which may be related with the level of pain experienced, affects care seeking. InTetteh et al (2017), the subjective value of administration mode, of dosing, of risk of adverse events and of the interruption of daily routine, were shown to in uence demand for medication.Objective factors such as gender, income and access to health facilities were also found by other studies to be insigni cant predictors(Seid and Metaferia, 2018, Tetteh et al, 2017, Datiko et al, 2020, Diaz et al, 2013. Notwithstanding, education is generally found to be relevant (Tetteh et al, 2017, Seid and Metaferia, 2018) but it is not fully correlated with health literacy (i.e., the capacity to recognize symptoms and illness and to make decisions to prevent or manage them) which may be a stronger force behind healthcare demand(Suka et al, 2016).5.2 Other factors not controlled for and policy implicationsSome words are merited on the macroeconomic factors that were not directly controlled for.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…These two papers imply that subjective misevaluation of disease severity, which may be related with the level of pain experienced, affects care seeking. InTetteh et al (2017), the subjective value of administration mode, of dosing, of risk of adverse events and of the interruption of daily routine, were shown to in uence demand for medication.Objective factors such as gender, income and access to health facilities were also found by other studies to be insigni cant predictors(Seid and Metaferia, 2018, Tetteh et al, 2017, Datiko et al, 2020, Diaz et al, 2013. Notwithstanding, education is generally found to be relevant (Tetteh et al, 2017, Seid and Metaferia, 2018) but it is not fully correlated with health literacy (i.e., the capacity to recognize symptoms and illness and to make decisions to prevent or manage them) which may be a stronger force behind healthcare demand(Suka et al, 2016).5.2 Other factors not controlled for and policy implicationsSome words are merited on the macroeconomic factors that were not directly controlled for.…”
supporting
confidence: 64%
“…A recent large international survey, conducted by Velden et al (2020), with 5,196 individuals from seven developed and seven developing countries including Brazil, estimated that only 30% of patients with sore throat, a symptom associated with In uenza-like illnesses and acute respiratory illnesses (Zhang et al, 2020), seek a general practitioner. Similarly high rates of refusal and also delay in seeking care were found in national-level surveys (Datiko et al, 2020, Seid and Metaferia, 2018, Zhang et al, 2020, Suka et al, 2016. These behaviours besides prolonging the impairment of own health and labour productivity (Piabuo and Tieguhong, 2017), and increasing risk of own mortality, which already have social consequences, may also increase contagion locally in case of viral and bacterial diseases (Datiko et al, 2020, Seid andMetaferia, 2018).…”
Section: Background 20 Motivationmentioning
confidence: 82%
“…A preliminary analysis on the HSD comparing the two periods found that there was, on average, an increase of 1 day. Although this increase was statistically significant, we did not consider this delay as clinically significant; we, thus, evaluated only characteristics potentially associated with a long PD, (>30 days) [36], using logistic regression models both univariate and multivariate, with backward selection (p = 0.20). The data were analyzed using Stata software, release 15.0.…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated total diagnostic delay (TD) as the time interval between the onset of symptoms and start of TB treatment. This included patient delay (PD) and health system delay (HSD); PD: period from the onset of the first symptom(s) related to pulmonary TB to the first medical consultation; HSD: the time interval between the first medical consultation and start of TB treatment [35,36].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Ensuring early diagnosis and prompt initiation of treatment can reduce TB transmission and improve individual health outcomes whilst reducing disability [2][3][4][5] . However, the effectiveness of TB diagnostic interventions in health systems are limited as poverty and high out of pocket expenditure are barriers to patients seeking TB diagnosis and treatment in LMICs [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%